1997
DOI: 10.1111/j.1439-0434.1997.tb00405.x
|View full text |Cite
|
Sign up to set email alerts
|

A Serious Disease of Groundnut Caused by Cowpea Mild Mottle Virus in the Sudan

Abstract: A serious disease of groundnut (Arachis hypogaea L.) characterized by stunting of plants, downward roUing, mottling, general chlorosis and reduced size ofthe leaflets was observed in the Sudan, Surveys conducted from 1992 to 1994 showed that this disease was restricted to irrigated groundnut crops grown between the two Niles, The virus had slightly fiexuous filamentous particles (626 nm long) and was transmitted by whiteflies. It was identified seroiogically as cowpea mild mottle virus (CPMMV), This appears to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Naturally infected cowpea plants exhibit either a mild systemic mottle or are symptomless. Differences in symptom severity in cowpea plants make economic assessment of the disease difficult, but it is nonetheless considered a definite threat to the successful production of such legumenous crops as soybeans, peanuts, beans and mungbeans, all of which are intercropped with cowpeas in many tropical countries in Africa and Asia [6,16,23].…”
Section: Introductionmentioning
confidence: 99%
“…Naturally infected cowpea plants exhibit either a mild systemic mottle or are symptomless. Differences in symptom severity in cowpea plants make economic assessment of the disease difficult, but it is nonetheless considered a definite threat to the successful production of such legumenous crops as soybeans, peanuts, beans and mungbeans, all of which are intercropped with cowpeas in many tropical countries in Africa and Asia [6,16,23].…”
Section: Introductionmentioning
confidence: 99%
“…'Wilis' did not affect the plant height and number of leaves. This is different from CPMMV infection in the groundnut in Sudan, which caused stunting, reduction of internodes length, and leaf [7]. Remarks: Means within a column followed by the same letter are not significantly different at 0.05 level in a DMRT, α = 5% *Abnormal seed was indicated by discoloration and malformation of seed (black and wrinkled seed)…”
Section: Figure 1 Development Of Mottle Disease On 'Wilis'mentioning
confidence: 91%
“…CPMMV has become a severe problem in Sudan [7]. Offei and Albrechtsen [8] reported that infection of CPMMV on Bambara groundnut (Vigna subterranea L.) caused a reduction in the number of pods, seeds, and seed weight.…”
Section: Introductionmentioning
confidence: 99%
“…In general, carlaviruses are both sap-transmitted and transmitted by aphids (King et al 2011). Several aphid species (Aphis craccivora, A. glycines, A. gossypii, A. spiraecola, Myzus persicae) have therefore been tested as possible vectors of CPMMV yet none of these were able to transmit the virus (Iwaki et al 1982;Thouvenel et al 1982;El-Hassan et al 1997;Mansour et al 1998). This led to the discovery that CPMMV is an exception among carlaviruses, being transmitted by the whitefly Bemisia tabaci (Hemptera: Aleyrodidae) (Iwaki et al 1982;Munyappa and Reddy 1983;Jeyanandarajah and Brunt 1993;Naidu et al 1998;Marubayashi et al 2010).…”
Section: Transmission Modementioning
confidence: 99%
“…The virus was subsequently described in Sudan infecting irrigated groundnut during the 1992-1994 seasons. Over the period of 3 years, the incidence in groundnut fields usually ranged between 10 and 50%, but in some fields amounted to 100% (El-Hassan et al 1997), with losses of 10-100%.…”
Section: The Spread Of Cpmmv Globally and In Brazilmentioning
confidence: 99%